Technology Transfer Agreement for Developing Countries - Wionczek, Miguel (1971)
The purpose of this paper is to propose a basis for a detailed study on technology transfer to Mexico through agreements between companies, in accordance with the recommendations of the United Nations Consultative Committee on the Application of Science and Technology to Development. The article understands that technology transfers cover not only patented knowledge but also transfers of know-how in various fields, such as product research and design; engineering, selection and procurement of machinery, among others. All this, thanks to the different contractual agreements between companies from developed and underdeveloped countries. To this extent, the author discusses five categories of contractual agreements, examining the advantages and disadvantages that will affect the contracting parties, and also assesses the impact of such agreements on the economy of the recipient country. The article concludes by pointing out that technology transfer agreements can be considered an important source for strengthening and developing the economy of developing countries.